Cross-cultural contexts of metaphysics - Barkovskaja, Alla V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
It is determined that the concept «metaphysics» has a number of historical interpretations in European philosophy which caused interest in the consideration of this phenomenon in the Eastern ethno-cultural space. An attempt to identify the preferences and specificity of metaphysical concepts of the cultures of Greece, China, India and Russia has been made. It was found out that the categorical apparatus of metaphysics is characterised by both cross-cultural universality and features peculiar only to a particular ethnos.
Keywords: metaphysics; wisdom; absolute; God; brahman; atman; shunyata; tao; culture